DEVELOPMENT OF VIDEOS TUTORIAL MEDIA FOR INTERNATIONAL BRIDAL MAKE UP BASED ON HYBRID LEARNING BY UTILIZING SIPDA UNIMED LEARNING MANAGEMENT SYSTEM - Tobing, Marnala; Dhana, Vita Pujawanti; Rangkuti, Irmiah Nurul; Sitompul, Astrid (Journal of Community Research and Service, 2024)
This study aims to develop an International bridal makeup videos tutorial on hybrid learning  by utilizing learning management system SIPDA Unimed. This Reaseach is use Research and Development using the ADDIE development model which consists of 5 (five) steps or development phases including: (A)nalysis, (D)esign, (D)evelopment,(I) mplementation and (E)valuate. Data collection is carried out through expert tests including tests of media experts, design experts and material experts. After an evaluation from experts, it was continued with trials on respondents, esspeciallay students of the cosmetology education study program through individual tests (one to one), small group tests (Small Group) and Field Tests (field tests). This research will produce learning videos tutorial output in International bridal cosmetology videos learning include Japanese bridal cometology, Korean bridal cosmetology, Indian bridal Cosmetology, Chinese bridal cosmetology, and Pakistani bridal cosmetology. This research has met the Level of Technological Preparedness (TKT) 4-6, namely: 1 )Data Collection, Validation in Simulation Environments, 2) Completeness and Analysis of Data on Simulation Environments, 3) Important and significant of development results for decision and policy support. The hypothesis result testing prove that: (1) Learning videos are eligible for use in (2) there  is a significant difference between  student learning outcomes  that studied using learning videos media. This is indicated by the results of data processing (tcount =3,285 )at the level of significance É” = 0.05 with dk 56,3 obtained (ttable = 1.65 ), so (tcount >  ttable),the effectiveness of advantage tutorial videos media in international bride cosmetology videos tutorial= 80.50%. This is indicated that the implementation of The International bridal makeup videos based on Hybrid Learning by utilizing the SIPDA Unimed Learning Management System are more effective in improving students competence and knowledge on The International bridal makeup hybrid learning.